The Fullness of the Logos in the Key of Life Book I The Case of God in the New Enlightenment - Tymieniecka, Anna-Teresa (Analecta Husserliana, The Yearbook of Phenomenological Research, 2009)
Lamentations over the disarray and disorientation in the philosophical quest may be heard from all sides today. The horizon of the All no longer beacons, for our hope of attaining it seems ever to recede. Yet, challenging the mistrust of reason that pursuit is precisely engaged in what is undertaken here. Our forty-year elaboration of the ontopoiesis/phenomenology of life as first philosophy/phenomenology in its unravelling of the metamorphic deployment of the logos of life has laid the foundations for the retrieval of the metaphysical vision. Here the classic concerns of philosophy are not negligently dismissed but are ciphered afresh in the light of innumerable perspectives and insights brought to philosophical attention in a New Enlightenment by advances in the sciences of life and of human apprehension. Strikingly enough pursuit of the greatest enigma of all, namely, that of the All enhancing Divine, is revived in the revelation that the logos informing life is the Fullness of God. In the Fullness being revealed in the infinite intricacies of the operations of the Logos of Life, we find the plenitude of God's experiencing man. In times when the prevailing critique of reason casts aspersions on the quest for God through reason, the full revelation of the logos brings to the entire human experience the infinities of God. In logos omnia.